2020
DOI: 10.1111/ane.13290
|View full text |Cite
|
Sign up to set email alerts
|

Non‐motor symptoms are associated with midline tremor in essential tremor

Abstract: including cognition deficiency, psychiatry symptoms, sleep disruption, and sensory abnormalities, has recently been reported in ET syndrome. 2 Besides, accumulating evidence on different etiologies, pathophysiologies, and clinical features has demonstrated the heterogeneity of ET syndrome, even giving rise to a new placeholder, ET-plus. 2,3 Due to such heterogeneity, its disease sub-types should be extensively studied to understand the inherent mechanisms of ET syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Essential tremor was defined as an Axis 1 tremor syndrome with "isolated tremor syndrome of bilateral upper limb action tremor" of "at least 3 years' duration" in the "absence of other neurological signs, such as dystonia, ataxia, or parkinsonism". "Essential tremor plus" was adopted to describe tremor with the characteristics of ET as well as "additional neurological signs of uncertain significance" [1], in order to accommodate the additional movement disorders and non-motor symptoms increasingly described in ET patients [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Essential tremor was defined as an Axis 1 tremor syndrome with "isolated tremor syndrome of bilateral upper limb action tremor" of "at least 3 years' duration" in the "absence of other neurological signs, such as dystonia, ataxia, or parkinsonism". "Essential tremor plus" was adopted to describe tremor with the characteristics of ET as well as "additional neurological signs of uncertain significance" [1], in order to accommodate the additional movement disorders and non-motor symptoms increasingly described in ET patients [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also reported that ET patients performed lower on certain sub-scores from the MMSE and MoCA including attention/calculation, construction, orientation, language, recall, visuospatial/executive, and abstraction (23,38,42). In a crosssectional study from China, 42% of patients with ET reported experiencing impaired concentration, while 60 and 27% of patients reported difficulties remembering things or events and remembering to do things, respectively (46). Patients with ET with midline tremor reported experiencing more impairment related to concentrating, remembering to do things, and remembering things or events compared to patients without midline tremor as assessed by the attention/memory domain of the NMSS (46).…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…Cognitive impairment was reported in a total of 26 studies across the US (11,(24)(25)(26)(27)(28)(29)(31)(32)(33)(34)(35)(36)(37)(38), Europe (23,39,40,48), 46,47), and Africa (45). The mean patient ages ranged from 25 to 87 years across included studies; eight publications assessed cognitive impairment specifically in older populations with mean patient ages >80 years (24,25,29,32,33,(36)(37)(38).…”
Section: Cognitive Impairmentmentioning
confidence: 99%
See 2 more Smart Citations